People's tribunals, human rights and the law searching for justice - Paulose, Regina Menachery (Routledge, 2020)
People's Tribunals are independent, peaceful, grassroots movements, created members of civil society, to address impunity that is associated with ongoing or past atrocities. As such, they offer society an alternative history and create a space for healing and reconciliation to take place that may otherwise be stifled by political agendas and legal technicalities. Since the 1960's, People's Tribunals have grown and developed to address many kinds of situations, from genocide to environmental degradation. This book presents a balance of academic and practitioner perspectives on Peoples' Tribunals. It explores key questions relating to their formation and roles and discusses what they can offer to victims and survivors. The volume provides an introduction to the subject, theoretically informed discussion reflecting different perspectives, and a range of contributions focusing on different types of Peoples' Tribunals and various aspects of their operation. The authors analyse advantages and disadvantages of these movements in a variety of contexts. The impact and contribution they have in the international criminal law and international human rights context is also discussed"--